Impact of New vs. Old International Children’s Continence Society Standardization on the Classification of Treatment Naïve Enuresis Children at Screening: The Value of Voiding Diaries and Questionnaires - Karamaria, Sevasti; Ranguelov, Nadejda; Hansen, Pernille; De Boe, Veerle; Verleyen, Pieter; Segers, Nathalie; Walle, Johan Vande; Dossche, Lien; Bael, An (Frontiers in Pediatrics, 2022)
Expert consensus papers recommend differentiating enuresis using questionnaires and voiding diaries into non- (NMNE) and monosymptomatic (MNE) is crucial at intake to decide the most appropriate workout and treatment. This national, Belgian, prospective study investigates the correlation, consistency, and added value of the two methods, the new against the old International Children’s Continence Society (ICCS) definitions, and documents the prevalence of the two enuresis subtypes in our population. 90 treatment-naïve enuretic children were evaluated with the questionnaire, and the voiding diary and the two clinical management tools were compared. Almost 30% of the children had a different diagnosis with each method, and we observed inconsistencies between them in registering Lower Tract Symptoms (κ=-0.057 – 0.432 depending on the symptom). Both methods had a high correlation in identifying MNE (rs=0.612, p=0.001) but not for NMNE (rs=0.127, p=0.248). According to the latest ICCS definitions, the incidence of MNE was significantly lower (7% vs. 48%) with the old standardization. Conclusion: The voiding diary and the questionnaire, as recommended by the ICCS at the screening of treatment-naïve enuretic patients, are considerably inconsistent and have significantly different sensitivity in identifying LUTS and thus differentiating MNE from NMNE. However, the high incidence of LUTS and very low prevalence of MNE suggest that differentiating MNE from NMNE to the maximum might not always correlate with different therapy-response.